The influence of social alienation on maintenance hemodialysis patients’ coping styles: chain mediating effects of family resilience and caregiver burden - Liu, Qiaoling; Zhang, Li; Xiang, Xia; Mao, Xiaoying; Lin, Ying; Li, Jingfeng; Cui, Wen (Frontiers in Psychiatry, 2023)
Objective: Research on the possible impact of social alienation, family resilience, and caregiver burden on the coping styles of Chinese patients on maintenance hemodialysis (MHD) is scarce. We explore the influence of social alienation, family resilience, and caregiver burden on the coping styles of MHD patients, both directly and indirectly. Methods: We invited 173 MHD patients and their primary caregivers for a cross-sectional study; the study using convenience sampling method at the hemodialysis center of the First People's Hospital of Foshan. The Chinese version of the Generalized Social of Alienation Scale, the Chinese version of the Simplified Coping Style Questionnaire, and a sociodemographic questionnaire were completed by the MHD patients, while their primary caregivers had filled out the Chinese Family Resilience Assessment Scale, the Chinese Version of the Zarit Caregiver Burden Interview, and provided socio-demographic information. SPSS macro program PROCESS v3.3 Model 6 were used for analyses of chain-mediated effects. Results: In the mediating effects model, the direct influence of social alienation upon coping styles was significant (95% CI -0.050, -0.014), and social alienation indirectly impacted coping style by family resilience in a significant way (95% CI -0.012, -0.001) or caregiver burden (95% CI -0.013, -0.001). In addition, social alienation significantly impacted coping style by both family resilience and caregiver burden (95% CI -0.008, -0.001). Conclusions: Social alienation can exert both a direct and indirect influence on coping styles through the mediating factors of family resilience and caregiver burden. Clinicians can take interventions to strengthen family resilience and reduce caregiver burden, which may be useful in improving socially isolated behaviors and coping skills in MHD patients.